Tabletted guar gum microspheres of piroxicam for targeted adjuvant therapy for colonic adenocarcinomas. (November 2012) - Vats, Anima; Pathak, Kamla
Background: In recent years, nonsteroidal anti-inflammatory drugs have been found to be cogent as an adjuvant therapeutic agent in mitigating colorectal cancer. Thus, this present investigation was aimed to formulate an oral, targeted tablet of piroxicam microspheres for sustained and targeted adjuvant therapy for colonic adenocarcinomas.Results: Crosslinked guar gum microspheres of piroxicam were directly compressed into matrix tablet and coated with Eudragit S100. The optimized tablet that displayed 0% release in simulated gastric fluid, 15% in simulated intestinal fluid and 97.1% in simulated colonic fluid underwent roentgenographic study in rabbits to check its safe transit to the colon. x-ray images revealed intactness of the tablet until it reached the colon where the tablet matrix eroded.Conclusion: The designed, conceptual formulation emerged as potential carrier for targeted adjuvant therapy of piroxicam.